A Study on the Fermionic 𝑝-Adic 𝑞-Integral Representation on ℤ𝑝 Associated with Weighted 𝑞-Bernstein and 𝑞-Genocchi Polynomials - Serkan Araci; Dilek Erdal; Jong Jin Seo (Abstract and Applied Analysis)
We consider weighted 𝑞-Genocchi numbers and polynomials. We investigated some interesting properties of the weighted 𝑞-Genocchi numbers related to weighted 𝑞-Bernstein polynomials by using fermionic 𝑝-adic integrals on ℤ𝑝.